DETERMINAN RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suci Wahyuliza; Ira Gustina; Nurfitriyenny Nurfitriyenny (Ensiklopedia of Journal, 2023)
The purpose of this study was to determine the effect of accounting profit, ROA, and total cash flow in LQ45 companies listed on the Indonesia Stock Exchange (BEI). This type of research is a quantitative study using descriptive methods. Sources of data used in this study are secondary data, namely data obtained indirectly by studying literature or documents related to the financial statements under study. The secondary data needed in this study is the company's financial data obtained from the company's annual financial statements LQ45 for the 2016-2018 period which have been published on the Indonesia Stock Exchange (IDX). The total sample used in the study were 10 LQ45 companies selected using purposive sampling technique. The data analysis technique used multiple linear regression. The results showed that accounting profit had no significant effect on stock returns, ROA had no significant effect on stock returns and total cash flow had a significant effect on stock returns.